Phase I and scintigraphy studies to evaluate safety, tolerability, pharmacokinetics, and lung deposition of inhaled GDC‐0214 in healthy volunteers. Issue 5 (26th February 2022) - Zhu, Rui; Chen, Hubert; Galanter, Joshua; She, Gaohong; Cai, Fang; Durk, Matthew R.; Zou, Yixuan; Chen, Liuxi; Kenny, Jane R.; Vadhavkar, Shweta; Warren, Simon; Taylor, Glyn; et al.
Abstract: Several inflammatory cytokines that promote inflammation and pathogenesis in asthma signal through the Janus kinase 1 (JAK1) pathway. This phase I, randomized, placebo‐controlled trial assessed the pharmacokinetics and safety of single and multiple ascending doses up to 15 mg twice daily for 14 days of a JAK1 inhibitor, GDC‐0214, in healthy volunteers (HVs; n  = 66). Doses were administered with a dry powder, capsule‐based inhaler. An accompanying open‐label gamma scintigraphy study in HVs examined the lung deposition of a single dose of inhaled Technetium‐99m ( 99m Tc)‐radiolabeled GDC‐0214. GDC‐0214 plasma concentrations were linear and approximately dose‐proportional after both single and multiple doses. Peak plasma concentrations occurred at 15–30 min after dosing. The mean apparent elimination half‐life ranged from 32 to 56 h across all single and multiple dose cohorts. After single and multiple doses, all adverse events were mild or moderate, and none led to treatment withdrawal. There was no clear evidence of systemic toxicity due to JAK1 inhibition, and systemic exposure was low, with plasma concentrations at least 15‐fold less than the plasma protein binding‐corrected IC50 of JAK1 at the highest dose. Scintigraphy showed that approximately 50% of the emitted dose of radiolabeled GDC‐0214 was deposited in the lungs and was distributed well to the peripheral airways. 99m Tc‐radiolabeled GDC‐0214 (1 mg) exhibited a mean plasma Cmax similar to that observed in phase I at the same dose level. Overall, inhaled GDC‐0214 exhibited pharmacokinetic properties favorable for inhaled administration.